2010
DOI: 10.1007/s11745-009-3382-7
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method for Determining Medium‐ and Long‐Chain FAMEs Using Gas Chromatography

Abstract: The existing protocols for analyzing fatty acid methyl esters (FAMEs) using a one-step acetyl chloride (AC) catalyzed transesterification and extraction procedure cannot accurately determine the medium- and long-chain fatty acids simultaneously in clinical (enteral, parenteral) formulations. For example: (1) addition of AC at room temperature generates an exothermic reaction that often results in loss of sample and possible injury to the analyst; (2) certain polyunsaturated fatty acids (PUFAs) are less stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Acetyl chloride (AcCl) was then added to the cooled methanol and shaken to ensure even dissolution. Previous authors have noted the exothermic reaction between AcCl and methanol and recommended keeping the reaction mixture cold over dry ice while slowly adding AcCl . However, we found that pre‐cooling the methanol was a more convenient approach that rendered the reaction much less violent.…”
Section: Methodsmentioning
confidence: 75%
“…Acetyl chloride (AcCl) was then added to the cooled methanol and shaken to ensure even dissolution. Previous authors have noted the exothermic reaction between AcCl and methanol and recommended keeping the reaction mixture cold over dry ice while slowly adding AcCl . However, we found that pre‐cooling the methanol was a more convenient approach that rendered the reaction much less violent.…”
Section: Methodsmentioning
confidence: 75%
“…An internal standard (C23:0) was added to 500 μl of cell lysate and a portion of the remaining 100 μl was used to establish a protein concentration in order to normalize fatty acid content to the amount of protein present. Lipids were extracted with chloroform: methanol (2:1) using the Folch method50 and fatty acids were converted into methyl esters at room temperature for 24 hours as described previously 51. The fatty acids were separated on a gas chromatography system equipped with an auto sampler, flame ionizing detector (GC2010; Shimadzu Corporation, Kyoto, Japan), and a Zebron ZB-WAX plus column (100 m, 0.25 mm ID, 0.25 m; Phenomenex, Torrance CA).…”
Section: Methodsmentioning
confidence: 99%
“…A subset of the lipid extracts was transesterified and analyzed by GC-MS using a modified version of the procedure by Xu et al [30]. 250 µl of extract were transferred to an 8 ml glass tube with a Teflon-lined lid.…”
Section: Transesterification and Gc-msmentioning
confidence: 99%